FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUASAN PELANGGAN DI BALLEZZA CAFE AND RESTO MAKASSAR - Fahrina Mustafa (Jurnal Bisnis dan Kewirausahaan, 2017)
This study aims: to determine whether factors such as pricing policies, promotion and support facilities effect on customer satisfaction and to identify the factors most dominant influence on customer satisfaction in Ballezza Cafe and restaurant Makassar. This study used a multiple regression method. The research data used were obtained from interviews, documentation and questionnaires. The results of this study show that: 1) the pricing policy partially positive and significant impact on customer satisfaction in Ballezza Cafe and restaurant Makassar, 2) promotion of partial positive and significant impact on customer satisfaction in Ballezza Cafe and restaurant Makassar, 3) support facilities in partial positive and significant impact on customer satisfaction in Ballezza Cafe and restaurant Makassar, and 4) the pricing policy, promotion and support facilities simultaneously positive and significant impact on customer satisfaction in Ballezza Cafe and restaurant Makassar. And variable price policy is the variable most dominant influence on customer satisfaction in Ballezza Cafe and restaurant Makassar.